The origin of Alzheimer’s disease: Prions? - Dongchuan Yang; Man Wang (Neurology Letters)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disorder, yet its aetiology remains contested. During the last two decades, evidence has accumulated that the two signature lesions of AD—amyloid‑β (Aβ) plaques and tau neurofibrillary tangles—behave as bona‑fide prions: misfolded protein assemblies capable of self‑replication, molecular strain variation and, under rare conditions, transmission between individuals. Viewing AD through the prion lens reconciles the stereotyped spread of pathology, the existence of clinicopathological subtypes, and the occurrence of iatrogenic cases. Here we provide an extended review of the prion hypothesis of AD, organised into five sections. First, we trace the historical evolution of the prion concept and its import for AD research. Second, we dissect the molecular and cellular mechanisms that enable Aβ and tau to acquire and propagate prion states. Third, we appraise experimental transmission studies, including synthetic and brain‑derived seeds, with emphasis on strain biology and cross‑species barriers. Fourth, we synthesise clinical and epidemiological observations ranging from inherited and sporadic forms to documented acquired cases. Fifth, we discuss translational ramifications—biomarkers, therapeutics and public‑health safeguards—and outline key knowledge gaps. Although AD lacks epidemic behaviour and therefore differs from classical prion diseases, the cumulative data support classifying it as a “double‑prion” disorder in which ageing, genetics and environment converge to initiate and propagate proteopathic seeds. Recognising the prionicity of Aβ and tau refines disease models and illuminates new avenues for early detection and intervention.